JNCI cancer spectrum: journal of the National Cancer Institute (Oxford Univ. Press, 2002)
JNCI Cancer Spectrum includes NCI's Physician Data Query (PDQ®) database; cancer statistics from NCI's Surveillance, Epidemiology, and End Results program; a database of oncology drugs from the Physicians' Desk Reference; abstracts of Cochrane Reviews (systematic evidence analyses) on cancer-related topics; an enhanced cancer news page; topical collections of "classic" (highly cited) articles (some with accompanying perspective articles), review articles, and book reviews; a searchable calendar of events; and a collection of useful links to cancer-related Web sites ### The Journal of the National Cancer Institute is the worldís top research journal in oncology. JNCI Cancer Spectrum will contain the full content of the printed Journal dating back to 1995, plus tables of contents back to 1989. In addition, it will contain extended news coverage (including weekly updates), an easily searchable online calendar, and topical collections of highly cited articles, review articles, book reviews, and Stat Bites. JNCI Cancer Spectrum will deliver the quality content you already find in the printed Journal with new online features to make it easier to use.
Gesehen am 12.12.2003
Keywords: Zeitschrift; Online-Ressource; Krebs; Onkologie